2011
DOI: 10.1021/co100075f
|View full text |Cite
|
Sign up to set email alerts
|

High Throughput Methodology for Synthesis, Screening, and Optimization of Solid State Lithium Ion Electrolytes

Abstract: A study of the lithium ion conductor Li(3x)La(2/3-x)TiO(3) solid solution and the surrounding composition space was carried out using a high throughput physical vapor deposition system. An optimum total ionic conductivity value of 5.45 × 10(-4) S cm(-1) was obtained for the composition Li(0.17)La(0.29)Ti(0.54) (Li(3x)La(2/3-x)TiO(3)x = 0.11). This optimum value was calculated using an artificial neural network model based on the empirical data. Due to the large scale of the data set produced and the complexity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 34 publications
(66 reference statements)
0
33
0
1
Order By: Relevance
“…80,81 HTE has thus far focused on solid state electrolytes, with a strategy of small compositional changes within one structure or compound family. For example, Beal et al 82 screened solid solution compositions in Li 3x La 2/3-x TiO 3 for fast Li conductivity and Yada et al 83 identified promising highly conducting dielectric interlayers for solid state Li batteries in the Li-NbTa ternary oxide system.…”
Section: Energy Conversion: Thermoelectricsmentioning
confidence: 99%
“…80,81 HTE has thus far focused on solid state electrolytes, with a strategy of small compositional changes within one structure or compound family. For example, Beal et al 82 screened solid solution compositions in Li 3x La 2/3-x TiO 3 for fast Li conductivity and Yada et al 83 identified promising highly conducting dielectric interlayers for solid state Li batteries in the Li-NbTa ternary oxide system.…”
Section: Energy Conversion: Thermoelectricsmentioning
confidence: 99%
“…These techniques require limited or no a priori assumptions about the underlying chemical process (Rutan et al, 2009; and have been flexibly applied to different analytical techniques. Nevertheless, to the authors' knowledge, only a few examples of application of MCR-ALS to X-ray diffraction data can be found in the literature (Rodriguez et al, 2007;Beal et al, 2011). In previous work (Taris et al, 2015), the EFA and MCR-ALS algorithms were implemented to monitor the setting reaction of a ceramic material.…”
Section: Introductionmentioning
confidence: 99%
“…xFeyO3-δ 79 , ferroelectricity in BixNa1-xTiyO3-δ 80,81 , tunable capacitors BaxSr1-xTiy03-δ 82 82 and BaxSr1-xTiyMn1-yO3-δ 83 , lithium electrolytes as LaxLi1-xTiyO3-δ 84 and electrocatalysis with SrxTi1-yFeyO3-δ 4 , LaxCa1-xMnyO3-δ 5 and LaxMnyNi1-yO3-δ 5 have all been studied using this approach. This broad range of applications have all required different type of substitution on either A-sites, B-sites, anionic sites or a combination of all the above.…”
Section: Perovskites Systems Studied By Ht-epvdmentioning
confidence: 99%
“…Therefore, when experimentally possible, it is preferred to synthesise the perovskites by in-situ direct crystallisation. A-site substitution has been the commonest approach with the studies of BixNa1-xTiyO3-δ as ferroelectrics 80,81 , BixNd1-xFeyO3-δ as piezoelectric 79 , BaxSr1-xTiyO3-δ as tunable dielectrics 82 , LaxLi1-xTiyO3-δ as lithium ion conductor 84 and LaxCa1-xMnyO3-δ as electrocatalysts. 5 Synthesis of the BixNa1-xTiyO3-δ, BixNd1-xFeyO3-δ and LaxLi1-xTiyO3-δ systems was done by depositing the constituent elements at moderate substrate temperature resulting in amorphous thin films which required a post deposition annealing step to form the perovskite structure.…”
Section: Synthesismentioning
confidence: 99%